Kuzma Minin’s Tomb in the Historiography of the 18th Century - A. A. Kuznetsov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2024)
This article traces how the idea that Kuzma Minin’s tomb is located in the Transfiguration Cathedral of Nizhny Novgorod developed in the 18th century and how it became intertwined with the narrative about Peter the Great visiting the place to venerate the relic. Together, these historical narratives formed an important plot determining the Russian socio-cultural identity. The analysis highlights a blurred boundary between pre-academic historiography and academic historical research. The methods used include a detailed study of historiographical sources and textual criticism. The belief in Kuzma Minin’s tomb within the cathedral stemmed from its burial records and commemoration lists. Their contamination led to such interpretations. Colonel A.I. Svechin was the first to suggest the idea in 1765. It was further developed by I.I. Golikov, a Russian historian, under the influence of Damaskin, the Bishop of Nizhny Novgorod, and cemented by N.S. Ilyinsky’s poem. The writings of I.I. Golikov and N.S. Ilyinsky rely on G.F. Müller’s scholarly work and link Kuzma Minin’s tomb to the image of Peter the Great paying homage to it.